A Critical Evaluation of English for Informatics ESP Textbook At Department of Informatics and Technology of University of Ma’arif Nahdlatul Ulama (UMNU) Kebumen - Hastri Firharmawan (ETERNAL (English Teaching Journal), 2016)
Having foremost significance in any ESP classroom, course readings are known as one of the most visible parts of any ESP instructing program. Playing a vital part where English is used as an outside dialect, such reading material ought to have a few highlights on which the needs and targets of an ESP teaching program are met. Concerning such a significance, making use of McDonough and Shaw’s (2003) model, this study evaluate fundamentally the current status of the ESP book used in English for informatics at UMNU Kebumen. The evaluation tries:1)to show the significance of ESP materials development as well as evaluation; (2) to present the fundamental drawbacks in the book; and, (3) to show some practical recommendation  and arrangements to handle the noteworthy issues and drawbacks of such ESP textbooks.